Legal Liability for Artificial Intelligence Decisions in the Indonesian Judicial System - Rizki Dwi Saputra (Veteran Law Review, 2025)
The rapid integration of Artificial Intelligence (AI) into judicial processes has created new challenges for Indonesia’s legal system, particularly in defining accountability and legal liability for AI-assisted decisions. This study aims to analyze how AI technologies can be harmonized with Indonesia’s legal framework while upholding judicial independence, transparency, and fairness. Using a normative legal research method, the study examines statutory provisions, doctrinal principles, and comparative practices from the European Union and the United States. The analysis reveals that current Indonesian lawssuch as Law No. 48 of 2009 on Judicial Power and Law No. 11 of 2008 on Electronic Information and Transactions do not yet regulate liability for AI-generated outcomes. Consequently, AI cannot be recognized as a legal subject, and responsibility remains with developers, operators, or judicial institutions. The study concludes that Indonesia must establish a specific legal framework defining human oversight, AI accountability, and ethical governance to ensure that technological innovation aligns with constitutional principles of justice and human rights. These findings contribute to the development of a transparent and responsible AI governance model within Indonesia’s judiciary.